Auditorio para la Universidad de Zurich (2000)
Obra de los arqs. <Gigon & Guyer>. Suiza, 1999. En construcción
Keywords: GUYER, MIKE; GIGON, ANNETTE; SUIZA; ZURICH; AUDITORIOS; UNIVERSIDADES; ARQUITECTURA EDUCACIONAL